DIGITAL DISTRACTIONS, SLEEP AND STUDENT PERFORMANCE: A STUDY ON GEN Z LEARNERS - Sharma, Harshal; Sharma, Preeti (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to identify and classify sleep patterns among Gen Z students, examining the impact of sleep on cognitive functions critical for academic success and overall well-being. Method: Utilizing a cross-sectional survey-based approach, the research collected data on sleep duration, quality, timing, and associated lifestyle factors, including digital habits, diet, and academic workload. Results: The findings reveal that irregular sleep patterns, excessive screen time, and academic pressures are major contributors to sleep deprivation among Gen Z students. Poor sleep quality is linked to diminished memory, concentration, and problem-solving abilities, as well as heightened stress, mood disturbances, and compromised physical health. Novelty: This study provides a comprehensive analysis of the multifactorial influences on sleep behavior among Gen Z students, highlighting the critical connection between digital lifestyles and sleep health. The insights gained advocate for targeted interventions by educators and policymakers to promote healthier sleep practices, underscoring the essential role of sleep in fostering cognitive performance and emotional resilience in the digital era.